Long-Term Results for a One-Stage Surgery Technique for Patients With Craniofacial Plexiform Neurofibroma. Issue 8 (November 2018) - Chen, Liangbo; Guo, Chengrui; Song, Xuefei; Yan, Chenxi; Hu, Xiaojie
Abstract : Background: Neurofibromatosis (NF) is an autosomal dominant genetic disorder, and NF type 1 (NF1) is one of the most common forms. Plexiform neurofibroma (PNF) is one of the characteristic expressions of NF1. The proper treatment for patients with craniofacial PNF is surgery. The evaluation methods for the surgical outcome of these patients are still controversial. As a consequence, a one-stage surgical technique and an appropriate evaluation method for patients with craniofacial PNF were discussed in this article. Methods: This research is a retrospective study. Nine patients with craniofacial PNF were included in this study. They had undergone a one-stage surgical technique of tumor debulking and nasolabial fold reconstruction. Three methods had been applied to evaluate the surgical outcome. Results: Significant improvement was observed in 8 patients. Eight patients were assessed by the relatively objective evaluation method. Obvious symmetry improvement was calculated using Mimics software in 7 patients. Conclusion: The surgical technique could achieve good surgical outcomes in both functional and cosmetic terms. Additionally, the relatively objective evaluation technique based on Mimics software could be a more convincing method for evaluating the surgical outcomes of craniofacial patients with PNF.